ELIMINATION OF GENDER BIAS IN LEARNING ARABIC/ ØØ°Ù Ø§Ù„ØªØÙŠØ² Ø§Ù„Ø¬Ù†Ø³ÙŠ ÙÙŠ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Nurcholis, Ahmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
It is not always true that the Arabic language contains absolute gender bias since in fact, the balaghah study has discovered that it respects and upholds women’s dignity for sure. Na’nak confirms this in his book ‘ Al Manar Fi Ulumil Balaghah which precisely describes Arabic as a language that upholds women’s dignity instead of being rooted on gender bias. Every ‘plural’ word is mu’annast, all objects in our galaxy is mu’annast majazy and there is shurah An Nisa’ in Holy Qur’an. We must be proud of Arabic because it is used as the official language of 22 countries of Arabic Nation League, which play essential role in Moslems’ lives throughout the world who speak around 150 millions local languages in western Asia and Nothern Africa. Under the Islan influence, this language colors the languages of Persia, Turkey, Urdu, Malay, Hausa, and Swahili. Arabic contributes 40-60 percent of vocabulary into these languages, and a strong influence on their syntax, nahwu, and literary works. Arabic is spoken as the religious language of Moslems in the world as well as the language of Islamic law. Finally, this language is of Islamic culture taught throughout thousands of schools outside the Arabic world, from Sinegal through Philipines. It is used as a language of learning, literature, and thoughts in history, ethics, law, fiqh, theology, and Islamic book study.